2022
DOI: 10.1038/s41467-022-31238-y
|View full text |Cite|
|
Sign up to set email alerts
|

Combinatorial immunotherapies overcome MYC-driven immune evasion in triple negative breast cancer

Abstract: Few patients with triple negative breast cancer (TNBC) benefit from immune checkpoint inhibitors with complete and durable remissions being quite rare. Oncogenes can regulate tumor immune infiltration, however whether oncogenes dictate diminished response to immunotherapy and whether these effects are reversible remains poorly understood. Here, we report that TNBCs with elevated MYC expression are resistant to immune checkpoint inhibitor therapy. Using mouse models and patient data, we show that MYC signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 75 publications
(99 reference statements)
1
27
0
Order By: Relevance
“…Likewise, suppressing MYC via epigenetic therapy reverted immune evasion in a mouse lung cancer model [ 118 ]. Finally, a retrospective analysis of several clinical studies suggested that elevated MYC expression might be associated with resistance to immune checkpoint inhibitor therapy in metastatic urothelial carcinoma and possibly other cancer types, including TNBC [ 119 ]. While the significance of these associations remains to be confirmed, the same study reported that MYC‐induced anti‐PD‐L1 resistance could be overcome with a combinatorial immuno‐therapeutic regimen in a preclinical model of TNBC.…”
Section: Myc and Therapy Resistancementioning
confidence: 99%
“…Likewise, suppressing MYC via epigenetic therapy reverted immune evasion in a mouse lung cancer model [ 118 ]. Finally, a retrospective analysis of several clinical studies suggested that elevated MYC expression might be associated with resistance to immune checkpoint inhibitor therapy in metastatic urothelial carcinoma and possibly other cancer types, including TNBC [ 119 ]. While the significance of these associations remains to be confirmed, the same study reported that MYC‐induced anti‐PD‐L1 resistance could be overcome with a combinatorial immuno‐therapeutic regimen in a preclinical model of TNBC.…”
Section: Myc and Therapy Resistancementioning
confidence: 99%
“…( E ) Pathway enrichment of DEGs shared between highly metastatic tumors. ( F ) Scatterplot shows the correlation of MYC (42) and immune regulation signature expression colored by tumor model. Pearson correlation coefficient is shown.…”
Section: Figure S1mentioning
confidence: 99%
“…MYC signaling was among the top 5 enriched pathways in highly metastatic primary tumors (Supplementary Figure S3E). MYC signaling can lead to evasion from immune surveillance by the suppression of interferon signaling and antigen-presentation pathways including the down-regulation of B2M and MHC-I (41, 42). This anti-correlation could explain the observed upregulation of immune regulatory pathways in poorly metastatic compared to highly metastatic primary tumors that showed elevated MYC signaling (Supplementary Figure S3F).…”
Section: Bc Pdx Models With Varying Metastatic Potential Show Transcr...mentioning
confidence: 99%
“…MYC can act as a transcriptional activator of PD-L1 [ 81 ]. It was shown to drive immune evasion by decreasing immune cell infiltration and HLA class I expression [ 82 ]. The downregulation of PTEN promoted the proliferation of NSCLCs by increasing the expression of PD-L1 [ 83 ].…”
Section: Correlations Between Hdac6 and Pd-l1mentioning
confidence: 99%